Análisis comparativo del clima organizacional en una institución educativa privada de Santa Marta de dos grupos de docentes y administrativos en el año 2023 (2024)
This paper focuses on analyzing the organizational climate in a private university in Santa Marta, assessing the perception of teachers and administrative staff at two different measures. The specific objectives include evaluating the work environment of both populations, analyzing differences between teachers and administrative staff, and formulating recommendations to enhance the work environment. A quantitative methodology and non-probabilistic sampling was used, with the "Instrument for Measuring Climate in Colombian Organizations (IMCOC)" 45 questions divided into seven variables.